Appraisal on social perception pertaining to communication and psychology - Abdul Hamid, Norashikin; Abdul Rahman, Raha; Mohd Masirin, Mohd Idrus; Setiawan, Muhammad Ikhsan; Mudjanarko, Iwan Sri Wiwoho; Salleh, Fauzilah (LPPM Narotama University, 2020)
The most complex mysteries we face in life are understanding people. We spend a lot of time thinking about others, trying to understand why they do what they do, whether they mean what they say and how they feel about us. Social psychologists refer to this process as social perception and it is a very central aspect of our existence as social beings. A socially competent person can make note of other people’s facial expressions, tone of voice, posture, gestures, words, and the like, and on the basis of these clues, make reasonably accurate judgments about that person’s state of mind, emotions, and intentions. Socially competent people then use these inferences about other people’s inner states to make good decisions about how to behave socially. Social perception is an important component of social competence and social success. In addition to social perception, socially competent people must have knowledge of social rules, roles, routines, and scripts in their social lives. Furthermore, they must make use of this knowledge and of these scripts in their decision making and acting. They also have a concern for other people and make it a habit to adjust their behaviour based on the needs of others. Finally, they have the confidence needed to interact socially and accept the vulnerability associated with potential rejection. This paper will discuss what is social perception, social perception aspects of non-verbal communication, attribution and impression formation and also some suggestion on how social perception affected cultures.